Pemaksimalan Branding Usaha Melalui Pemahaman Pentingnya Identitas Usaha Bagi Pelaku UMKM di Jorong Uba, Kecamatan Tilatang Kamang - Yani Maila Santi; Indah Respati Kusumasari (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Business identity is an important component for business progress. Many micro MSME actors underestimate the existence of a business identity. The existence of a business identity, indirectly the customer's business has a characteristic or differentiator with similar competitors' business products. In addition, having a business identity can indirectly promote and introduce products widely more quickly. During this assistance, micro, small and medium businesses are given knowledge about the importance of business identity and how to have a good and attractive business identity. This mentoring activity lasts for about 4 months and aims to develop micro businesses so that they can progress and develop. This activity was carried out in Jorong Uba, Tilatang Kamang District, the participants consisted of 2 people and 1 mentor who was experienced in their field. This series of mentoring activities will close with practice and creation of business identities for micro, small and medium businesses in Jorong Uba, Tilatang Kamang District. Keywords:,,,